PENANGANAN KETIDAKNYAMANAN KEHAMILAN SELAMA PANDEMI COVID-19 - Lestari, Pratiwi Puji; Aulia, Fika; Suryati, Suryati (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2021)
The limited access of pregnant women to health facilities during the COVID-19 pandemic does not allow pregnant women to have direct contact with health workers, so the need for information to deal with discomfort that commonly occurs in pregnant women must be met. The purpose is to provide an understanding of some of the physiological discomforts that occur in pregnant women, their causes, and how to overcome the discomfort. The method of implementing this community service activity includes socialization to the Coordinator Midwife of the Alalak Health Center for the implementation of community service activities regarding Handling Pregnancy Discomfort During the Covid-19 Pandemic. After the implementation of this community service activity, it is hoped that pregnant women can apply the simple solutions offered at home when experiencing state of discomfort.